The Effect of Type of Internal Control Report on Users’ Confidence in the Accompanying Financial Statement Audit Report* - ASARE, STEPHEN KWAKU; WRIGHT, ARNOLD (Contemporary Accounting Research, 2012)
We develop and test a model that links internal control over financial reporting (ICOFR) disclosures to users’ confidence in the standard audit report (SAR) on the financial statements. The model suggests that users’ confidence in the SAR is determined by the consistency of the message conveyed by the two audit reports. Based on this model, we hypothesize that users’ confidence in the SAR is lower in the presence of an entity level material weakness compared to an account specific material weakness and both confidence assessments are lower than the confidence assessments associated with the unqualified ICOFR report. We also propose that SAR confidence assessments affect investment judgments. We tested these hypotheses in two experiments. In Experiment 1, 65 equity analysts indicated their confidence in the SAR, assessed the risk of a stock price decline, and provided a stock recommendation on a public company that had received a SAR and an adverse ICOFR report (describing either an entity level or an account specific material weakness). In Experiment 2, 70 average investors evaluated the same company but were randomly assigned to three conditions (same adverse control conditions as in experiment 1 and an unqualified ICOFR condition). In addition, they provided assessments of information and verification risks, which allowed us to directly test our model. The findings are as hypothesized and support the notion that the apparent inconsistency between an adverse ICOFR report and the SAR undermines confidence in the SAR. Finally, confidence in the SAR affects investment judgments (risk of stock price decline) and decisions (stock recommendations).